Uteroplacental nutrient flux and evidence for metabolic reprogramming during sustained hypoxemia. Issue 18 (23rd September 2021) - Jones, Amanda K.; Rozance, Paul J.; Brown, Laura D.; Lorca, Ramón A.; Julian, Colleen G.; Moore, Lorna G.; Limesand, Sean W.; Wesolowski, Stephanie R.
Abstract: Gestational hypoxemia is often associated with reduced birth weight, yet how hypoxemia controls uteroplacental nutrient metabolism and supply to the fetus is unclear. This study tested the effects of maternal hypoxemia (HOX) between 0.8 and 0.9 gestation on uteroplacental nutrient metabolism and flux to the fetus in pregnant sheep. Despite hypoxemia, uteroplacental and fetal oxygen utilization and net glucose and lactate uptake rates were similar in HOX ( n  = 11) compared to CON ( n  = 7) groups. HOX fetuses had increased lactate and pyruvate concentrations and increased net pyruvate output to the utero‐placenta. In the HOX group, uteroplacental flux of alanine to the fetus was decreased, as was glutamate flux from the fetus. HOX fetuses had increased alanine and decreased aspartate, serine, and glutamate concentrations. In HOX placental tissue, we identified hypoxic responses that should increase mitochondrial efficiency (decreased SDHB, increased COX4I2 ) and increase lactate production from pyruvate (increased LDHA protein and LDH activity, decreased LDHB and MPC2 ), both resembling metabolic reprogramming, but with evidence for decreased ( PFK1, PKM2 ), rather than increased, glycolysis and AMPK phosphorylation. This supports a fetal‐uteroplacental shuttle during sustained hypoxemia whereby uteroplacental tissues produce lactate as fuel for the fetus using pyruvate released from the fetus, rather than pyruvate produced from glucose in the placenta, given the absence of increased uteroplacental glucose uptake and glycolytic gene activation. Together, these results provide new mechanisms for how hypoxemia, independent of AMPK activation, regulates uteroplacental metabolism and nutrient allocation to the fetus, which allow the fetus to defend its oxidative metabolism and growth. Abstract : Sustained late gestation hypoxemia induces metabolic adaptations in the placenta and the allocation of nutrients to the fetus. Our data support a fetal‐uteroplacental shuttle whereby uteroplacental tissues produce lactate as fuel for the fetus using pyruvate released from the fetus, rather than pyruvate produced from glucose in the placenta, given the absence of increased uteroplacental glucose uptake and glycolytic gene activation. These results provide new mechanisms for how hypoxemia, independent of AMPK activation and reduced blood flow, regulates uteroplacental metabolism and nutrient allocation to the fetus, which allow the fetus to defend its oxidative metabolism and growth.